Trends and Research Development of Differentiated Learning in Reading Improvement: a biblometric analysis - Perwitasari, Lina Adi; Winarni, Retno; Yulisetiani, Septi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
The problem of differentiated learning in improving reading ability is increasingly complex along with the diversity of student needs and the development of educational technology. Although there has been a lot of research in this field, there has been no biliometric study that systematically maps the development of the research. This study aims to analyze the trends and developments of differentiated learning research in the context of improving reading ability through a bibliometric approach. The research method used bibliometric analysis of 1,459 documents from the Scopus database for the 2014-2024 period, including analysis of publication trends, collaboration patterns, and mapping research topics using VOSviewer. The results of the study revealed three main findings: (1) there was a significant increase in the number of publications, especially after 2019, reaching more than 250 publications in 2024; (2) the collaboration pattern shows the dominance of institutions from the United States (400 publications), followed by China and Germany (125 publications each); (3) Keyword co- occurrence analysis reveals the evolution of research focus from conventional approaches to technology integration and learning innovation, with "differentiated instruction" as the central node that is connected to various aspects of reading learning. The implications of this research lie in understanding research trends and patterns that can help educators develop more effective differentiated learning approaches.